Enhancing energy efficiency of an existing housing stock - Izmaylova, K.V.; Kharchenko, L.A. (Ways to Improve Construction Efficiency, 2021)
The article analyzes domestic and international experience in the field of energy efficiency and energy security. Thus, it was important to adopt the Law of Ukraine "On the Energy Efficiency of Buildings", which introduced mandatory certification of buildings by energy consumption classes. The study of sources on the issues of effective energy consumption showed that issues related to improving the energy efficiency of buildings and structures are acquiring special relevance; the use of foreign models to improve the energy efficiency of the housing stock. Specific organizational and economic measures are highlighted that will help improve the energy efficiency of the national economy. The Swedish experience of using a modern cost model for the full period of operation ("General Concept") is studied, which aims to assess the economic results of investments in measures to improve the energy efficiency of the housing stock. The main principles of the modern cost model of the full operation period and the criteria for determining the number of necessary energy efficiency measures are considered. Analyzed "hard" (physical condition of the building) and "soft" (user behavior) measures that provide for the integrated energy efficiency of the building. The stages of the analysis according to the cost model of the full operation period are considered. The typical for Sweden ranges of the duration of energy efficient measures and the requirements for the internal rate of return, which depends on the general economic situation in the country and the terms of the loan, have been investigated. Based on the results of the energy audit of the ten-story building selected for the study and taking into account the experience of Sweden, a number of measures to improve energy efficiency are proposed and a calculation is given to ensure the energy efficiency of a residential building in Ukraine. Based on the results obtained, it can be concluded that there is a positive trend in this implementation. With the integrated use of all measures that will even allow you to save more, you can significantly improve the energy efficiency of the existing housing stock in Ukraine.